Peran Manajemen Diklat dalam Meningkatkan Kualitas Layanan Publik - Sri Devi Nurjanah; Hanif Arif Setiawan; Faza Herna Faradila; Susilo Surahman (Universitas Kapuas Sintang, 2026)
This study discusses the role of education and training management in improving the quality of public services in government agencies. The background of this study stems from the need to improve the competence of civil servants so that they are able to provide fast, accountable services that meet the demands of modern society. The purpose of this study is to determine how training management, from planning and implementation to evaluation, affects the improvement of ASN capabilities and professionalism. The method used is descriptive qualitative with a literature study and official document analysis approach. The results show that good training management can improve employees' technical knowledge, social skills, and professional attitudes. In addition, the use of participatory and technology-based learning methods such as e-learning has been proven to increase the effectiveness of training. Continuous evaluation is also an important factor in ensuring the success of training programs. Overall, this study confirms that professional training management oriented towards competency development is a long-term investment in efforts to improve the quality of public services and realize good governance.